Necrotizing Fasciitis Associated with Staphylococcus lugdunensis - Hung, Tony (Hindawi Publishing Corporation, 2012)

(untitled)
Necrotizing fasciitis is a life-threatening soft tissue infection that results in rapid local tissue destruction. Type 1 necrotizing fasciitis is characterized by polymicrobial, synergistic infections that are caused by non-Group A streptococci, aerobic and anaerobic organisms. Type 2 necrotizing fasciitis involves Group A Streptococcus (GAS) with or without a coexisting staphylococcal infection. Here we provide the first report of necrotizing fasciitis jointly associated with the microbes Group B Streptococcus and Staphylococcus lugdunensis. S. lugdunensis is a commensal human skin bacterium known to cause often painful and prolonged skin and soft tissue infections. To our knowledge, however, this is the first case of Staph. lugdunensis-associated necrotizing fasciitis to be reported in the literature.